The Use of Virtual Reality for Training in Securing the Functioning of Critical Infrastructure - Andrzej GRABOWSKI (Zastosowanie rzeczywistości wirtualnej do szkoleń w zakresie zabezpieczenia funkcjonowania infrastruktury krytycznej, 2020)
Our national security, economic prosperity and national welfare depend on a set of highly interdependent elements of critical infrastructure. Examples of critical infrastructure facilities include the national electricity grid, oil and gas systems, telecommunication and information networks, transportation networks, water systems and banking and financial systems. Given their importance, it is crucial to maintain the reliability of critical infrastructure facilities, especially power plants, both in times of peace and also in times of crisis or under conditions of attack. For this purpose, on the one hand, it is possible to improve and create new technical solutions supporting the restoration of the proper functioning of critical infrastructure facilities, such as remotely controlled mobile robots for example. On the other hand, it is important to prepare employees to operate in unusual conditions by organising appropriate training. In both cases, it can be useful to apply virtual reality techniques.
Keywords: Rzeczywistość wirtualna